(untitled) (Bangladesh Journal of Botany, 2020)
Fourteen cultivars of cucumber were screened for their resistance to the Southern root-knot nematode, Meloidogyne incognita (Kofoid and White) Chitwood in an in planta experiment. The pots were maintained in greenhouse with CRD for 50 days after inoculation. The cultivar DS92-05 induced significant mortality and was rated “moderately resistant (MR)”. This cultivar showed increase in plant growth parameters including vine length. The cultivars DS92-06, Laghman, Sultan and Desitype were moderately susceptible (MS). The cultivar Rehan and DS96-299 were rated susceptible (S) whereas DS97-299, Chaiya, Beitalpha, Alto, DS92-04 and Local were rated as highly susceptible (HS). DS92-05 is thus promising for sustainable agriculture, specially in those areas with high population density of Southern Root knot nematode.